Method for evaluating moisture absorption of semiconductor encapsulating material

CN122882249APending Publication Date: 2026-10-09CHIPMOS TECHNOLOGIES (SHANGHAI) LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611241814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明为克服现有技术的不足,提供一种半导体封装材料吸湿性能的评估方法,解决现有技术流程不规范、终点判定标准不统一、取样节点随意、测试数据重复性差,且缺少标准化水分扩散率、饱和体积吸湿量计算流程的问题,实现全流程标准化管控,提升测试数据准确度与可比性

Benefits of technology

[0041]1.标准化,消除人为误差:统一规定烘干、吸湿阶段的取样节点、称重时长、工序衔接时限、样品转移环境,同时量化终点判定规则,摒弃传统依靠操作人员经验判定的模式,大幅提升测试数据重复性,实现不同实验室之间数据可比对、可互认。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122882249A_ABST
    Figure CN122882249A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of semiconductor, in particular to a kind of evaluation method of moisture absorption performance of semiconductor packaging material.The present application relates to the technical field of semiconductor, in particular to a kind of evaluation method of moisture absorption performance of semiconductor packaging material.It includes the following steps: S1 sample preparation;S2 initial dehumidification;S3 constant temperature and humidity moisture absorption;S4 final dehumidification;S5 standardization parameter calculation: based on the data collected in steps S1 to S4, the reversible saturated moisture absorption mass, irreversible moisture absorption mass, saturated volume moisture absorption amount and moisture diffusion rate of sample are calculated;S6 result evaluation: according to the calculation result of step S5, the moisture absorption performance of material is evaluated, the higher the saturated volume moisture absorption amount, the worse the moisture resistance of material;The higher the moisture diffusion rate, the faster the moisture absorption rate of material;The higher the irreversible moisture absorption mass, the higher the long-term moisture aging risk of material;Compared with prior art, standardization, eliminate artificial error, strict environmental control, reduce system error, perfect parameter system, support engineering application, risk control is comprehensive, and test reliability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, and more specifically to a method for evaluating the moisture absorption properties of semiconductor packaging materials. Background Technology

[0002] Moisture absorption performance assessment is a core component of semiconductor packaging reliability verification. The test results directly determine whether the packaging material can meet the reliability requirements of the moisture sensitivity level (MSL), and it is also a crucial preliminary test to ensure the long-term stable operation of semiconductor devices. The test principle involves measuring the mass change of the packaging material under constant temperature and humidity conditions to determine the material's moisture saturation rate, moisture absorption rate, and drying characteristics. This allows for the assessment of whether the packaging material will experience delamination, cracking, or other failures due to internal moisture expansion during high-temperature processes such as reflow soldering.

[0003] Currently, the mainstream testing of moisture absorption performance of packaging materials in the industry mainly uses high-precision environmental test chambers combined with semi-automatic testing processes. However, existing technologies have many technical shortcomings and practical problems: 1. Lack of a standardized testing system: Existing publicly available technologies have not established unified rules for determining the drying endpoint and moisture absorption saturation endpoint, nor have they standardized sampling nodes, time limits for step connections, and environmental constraints for weighing. At the same time, there is a lack of standardized quantitative calculation processes for moisture diffusivity and saturated volume moisture absorption, which cannot provide accurate material parameter support for advanced packaging structure design and reliability simulation. 2. Unstandardized industry practices and poor data consistency: There are no unified standards for testing procedures. Different testing institutions and operators have significantly different methods for determining the baking endpoint, moisture saturation state, and weighing time window, resulting in poor repeatability of test results for the same batch of samples and a lack of data interoperability between different laboratories. Testing cycles are generally long. If fixed sampling nodes are not planned during the moisture absorption stage, key characteristic data can be easily lost, reducing the accuracy of the moisture absorption curve fitting and leading to misjudgments of the material's moisture saturation time. There are no unified standards for instrument use. Insufficient balance accuracy, environmental disturbances, and temperature and humidity control deviations can introduce weighing errors, with moisture absorption rate calculation deviations exceeding 0.01%, which can directly cause errors in MSL (Mean Susceptible Level) classification. The drying endpoint of sample pretreatment relies entirely on operator experience. If the material enters the moisture absorption stage before being completely dried, the moisture saturation rate data will systematically deviate from the true value.

[0004] To address the aforementioned issues, there is an urgent need for a dedicated method for evaluating the moisture absorption performance of semiconductor packaging materials that features standardized operating procedures, repeatable test results, standardized quantitative parameter calculation capabilities, and is fully compatible with the low moisture absorption levels and high reliability requirements of semiconductor packaging materials. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention provides a method for evaluating the moisture absorption performance of semiconductor packaging materials. It addresses the problems of non-standard processes, inconsistent endpoint determination standards, arbitrary sampling points, poor repeatability of test data, and the lack of standardized calculation processes for moisture diffusivity and saturated volume moisture absorption. This method achieves standardized control throughout the entire process and improves the accuracy and comparability of test data.

[0006] To achieve the above objectives, a method for evaluating the moisture absorption properties of semiconductor packaging materials is designed, comprising the following steps:

[0007] S1, Sample preparation: Select semiconductor packaged samples and record initial sample data;

[0008] S2, Initial Dehumidification: Place the sample in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH and bake it. Take samples and weigh them at the set time points, determine the drying endpoint according to the unified criteria, and record the first drying weight.

[0009] S3, Constant temperature and humidity dehumidification: Place the sample that has completed the initial dehumidification in a dehumidification chamber with a temperature of 30±10℃ and a relative humidity of 60±10%. Take samples and weigh them according to the grading rules of the intensive sampling period and the stable period. Determine the dehumidification saturation endpoint according to the unified criteria and record the saturated dehumidification weight.

[0010] S4, final dehumidification: Place the moisture-saturated sample in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH for more than 48 hours, take samples and weigh them according to the set time nodes, determine the drying endpoint according to the unified criteria, and record the second drying weight.

[0011] S5, Standardized parameter calculation: Based on the data collected in steps S1 to S4, the reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount and moisture diffusivity of the sample are calculated.

[0012] S6, Result Evaluation: Evaluate the material's moisture absorption performance based on the calculation results of step S5. The higher the saturated volume moisture absorption, the worse the material's moisture resistance; the higher the moisture diffusivity, the faster the material's moisture absorption rate; the higher the irreversible moisture absorption mass, the higher the risk of long-term damp heat aging of the material.

[0013] In steps S2-S4, the unified criterion is the determination condition for the drying or moisture absorption endpoint. Meeting any one of the following conditions is sufficient to determine that the corresponding endpoint has been reached:

[0014] The weight change rate of at least two consecutive weighing data does not exceed 0.002%;

[0015] The weight-time change curve has entered a linear steady-state phase;

[0016] The formula for calculating the single-weight change rate is: Single-weight change rate = (current weighing mass - previous weighing mass) / previous weighing mass × 100%.

[0017] In step S1, the initial sample data includes sample weight, total sample volume, and average sample thickness.

[0018] In step S1, the total weight of the sample is not less than 10g, the number of samples is not less than 5, and there are no air bubbles or impurities; the total volume of the sample is measured by the water displacement method; the average thickness of the sample is obtained by taking the arithmetic mean after measuring 5 different points on the sample.

[0019] In step S1, an electronic balance that meets the accuracy requirements is used to complete the balance preheating, leveling calibration and zeroing operations under a specified environment, and a clean and dry container is used for weighing.

[0020] In steps S2-S3, the entire process of transferring the sample between processes is completed in a drying oven with a relative humidity of ≤10%, and the connection time between adjacent processes does not exceed 30 minutes.

[0021] In step S2, the sampling rules are as follows: the first weighing point is after baking for 48 hours, and subsequent weighing is carried out every 12 hours, with each weighing session lasting no more than 5 minutes; if the sample shows abnormal conditions such as solder ball detachment or breakage, the sample group is discarded and resampled for testing.

[0022] In step S3, a low-speed uniform airflow is used inside the moisture absorption chamber, and the sample surface must not come into contact with liquid water inside the chamber. The sampling rules are as follows: the first 24 hours of moisture absorption is the intensive data collection period, and samples are taken and weighed at three fixed points: 8h, 16h, and 24h. After the initial 24 hours of moisture absorption is completed, samples are taken and weighed every 24 hours. After the cumulative moisture absorption time reaches 192 hours, samples are taken every 24 hours. The maximum total moisture absorption time is 200 hours. If the maximum time is reached and the moisture absorption is still not determined to be saturated, the test is terminated and noted in the test report.

[0023] In step S4, the sampling rules are as follows: the 24 hours before baking is the intensive data collection period, and samples are taken and weighed at three fixed nodes at 8h, 12h, and 24h; after the initial 24 hours of baking, samples are taken and weighed once every 12 hours; the weighing operation time between all adjacent nodes is controlled within 5 minutes.

[0024] In step S5, the calculation methods for reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount, and moisture diffusivity are as follows:

[0025] Reversible saturated moisture absorption mass: ;

[0026] Irreversible moisture absorption capacity: ;

[0027] Moisture absorption by saturated volume: ;

[0028] Moisture diffusivity: ;

[0029] in,

[0030] Total sample volume, in units of ;

[0031] The average thickness of the sample, in units of ;

[0032] The first dry weight, in units of ;

[0033] This is the saturated moisture-absorbing weight, in units of ;

[0034] This is the second dry weight, in units of ;

[0035] Temperature T, relative humidity Reversible saturated hygroscopic mass under the given conditions, in units of ;

[0036] The mass of irreversible moisture absorption is expressed in units of... ;

[0037] The half-saturation time is expressed in units of 1 / 2 oz. ;

[0038] This represents the saturated volumetric moisture absorption under corresponding temperature and humidity conditions, in units of... ;

[0039] D(T) is the water diffusivity at temperature T, in units of... .

[0040] Compared with the prior art, the present invention has the following advantages:

[0041] 1. Standardization to eliminate human error: Standardize the sampling points, weighing time, process connection time limits, and sample transfer environment for the drying and moisture absorption stages. At the same time, quantify the endpoint determination rules, abandon the traditional model that relies on the experience of operators, greatly improve the repeatability of test data, and realize the comparability and mutual recognition of data between different laboratories.

[0042] 2. Strict environmental control reduces system errors: Clearly defined standards for balance accuracy, preheating requirements, weighing environment, and temperature and humidity control of the oven and desiccant chamber mitigate weighing deviations caused by insufficient instrument accuracy and environmental disturbances, effectively controlling weighing errors within a specified range. Within this range, to avoid misjudgment of MSL humidity sensitivity level due to data deviation.

[0043] 3. Improve the parameter system to support engineering applications: Establish a complete set of quantitative calculation methods for reversible hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic capacity, and moisture diffusivity, and supplement the dimensions for irreversible moisture evaluation. This will not only enable the determination of material hygroscopic performance, but also provide accurate material basic parameters for semiconductor packaging structure design and reliability simulation.

[0044] 4. Comprehensive risk management and high test reliability: The system adds rules for parallel testing, handling of abnormal samples, and maximum moisture absorption time limits. It also standardizes sample transfer protection measures to avoid problems such as secondary moisture absorption and damage to the samples that could interfere with the test results. The entire method is highly practical and can be directly transformed into standardized operating procedures for enterprises and third-party testing institutions. Attached Figure Description

[0045] Figure 1 This is a flowchart illustrating the evaluation method of the present invention.

[0046] Figure 2 This is a schematic diagram of the sampling nodes and endpoint determination in the initial dehumidification stage of this invention.

[0047] Figure 3 This is a schematic diagram of the sampling nodes and endpoint determination during the constant temperature and humidity moisture absorption stage in this invention.

[0048] Figure 4 This is a schematic diagram of the sampling nodes and endpoint determination in the final dehumidification stage of this invention.

[0049] Figure 5 This is a schematic diagram of the test results in step S2 of this embodiment of the invention.

[0050] Figure 6 This is a schematic diagram of the test results in step S3 of this embodiment of the invention.

[0051] Figure 7 This is a schematic diagram of the test results in step S4 of this embodiment of the invention. Detailed Implementation

[0052] The present invention will now be further described with reference to the accompanying drawings.

[0053] like Figures 1 to 4 As shown, the method for evaluating the moisture absorption performance of semiconductor packaging materials in this embodiment includes the following steps:

[0054] S1, Sample preparation: Select semiconductor packaged samples and record initial sample data;

[0055] S2, Initial Dehumidification: The sample is placed in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH for baking. Samples are taken and weighed according to the set time nodes. The drying endpoint is determined according to the unified criteria, and the first drying weight is recorded. The temperature of 125℃ can efficiently desorb the physically adsorbed water in the material, and it is lower than the glass transition temperature of the epoxy molding compound, so it will not cause degradation of the material matrix or performance deterioration. The test conditions are completely aligned with the industry's mass production dehumidification process.

[0056] S3, Constant temperature and humidity dehumidification: Place the sample that has completed the initial dehumidification in a dehumidification chamber with a temperature of 30±10℃ and a relative humidity of 60±10%. Take samples and weigh them according to the grading rules of the intensive sampling period and the stable period. Determine the dehumidification saturation endpoint according to the unified criteria and record the saturated dehumidification weight.

[0057] S4, final dehumidification: Place the moisture-saturated sample in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH for more than 48 hours, take samples and weigh them according to the set time nodes, determine the drying endpoint according to the unified criteria, and record the second drying weight.

[0058] S5, Standardized parameter calculation: Based on the data collected in steps S1 to S4, the reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount and moisture diffusivity of the sample are calculated.

[0059] S6, Result Evaluation: Evaluate the material's moisture absorption performance based on the calculation results of step S5. The higher the saturated volume moisture absorption, the worse the material's moisture resistance; the higher the moisture diffusivity, the faster the material's moisture absorption rate; the higher the irreversible moisture absorption mass, the higher the risk of long-term damp heat aging of the material.

[0060] In steps S2-S4, the unified criterion is the determination condition for the drying or moisture absorption endpoint. Meeting any one of the following conditions is sufficient to determine that the corresponding endpoint has been reached:

[0061] The weight change rate of at least two consecutive weighing data does not exceed 0.002%;

[0062] The weight-time change curve has entered a linear steady-state phase;

[0063] The formula for calculating the single-batch weight change rate is: Single-batch weight change rate = (current weighing mass - previous weighing mass) / previous weighing mass × 100%. Semiconductor packaging materials have extremely low saturated moisture absorption. The 0.1% weight change rate criterion commonly used in general material testing is equivalent to a completely unsaturated state for semiconductor materials. The 0.002% threshold set in this embodiment is a balance judgment threshold set for the low moisture absorption level of semiconductor materials, ensuring that the material truly reaches moisture absorption / drying equilibrium and avoiding systematic data deviations due to lenient endpoint judgment.

[0064] In step S1, the initial sample data includes sample weight, total sample volume, and average sample thickness. The basic parameters of the sample are measured and archived before the initial dehumidification.

[0065] In step S1, the total sample weight is not less than 10g, the number of samples is not less than 5, and the samples are free of bubbles and impurities. The saturated moisture absorption of semiconductor packaging epoxy molding compound is usually only 0.05%~0.3% of the total sample weight, which is a milligram-level trace change. Setting a total sample weight of not less than 10g can amplify the absolute value of the moisture absorption mass, reduce the relative error of the balance, avoid data distortion due to insufficient moisture absorption, and ensure the accuracy of MSL humidity sensitivity level determination. The total sample volume is measured by the water displacement method. The average sample thickness is obtained by taking the arithmetic mean after measuring 5 different points on the sample.

[0066] In step S1, an electronic balance meeting the required accuracy is used. Under specified conditions, the balance is preheated, leveled, and zeroed. Weighing is then performed using a clean, dry container. Specifically, the electronic balance must meet two accuracy requirements: an accuracy of no less than 0.01 mg and an accuracy of no less than 0.001% of the total sample weight. The balance is placed on a level, vibration-free work surface, and the preheating time is no less than 60 minutes. The weighing environment temperature is controlled at 25℃±2℃, and the relative humidity is controlled at 45%±5%. During the weighing process, the ion fan is turned off, and personnel movement is prohibited to minimize weighing errors. The hygroscopic properties of semiconductor packaging materials directly determine whether fatal failures such as the popcorn effect and interface delamination will occur during reflow soldering. The industry has extremely low tolerance for deviations in hygroscopicity testing. General material hygroscopicity testing commonly uses a 0.1 mg accuracy balance, whose error is sufficient to lead to misjudgment of the MSL (Mean Susceptibility Level). This embodiment sets dual precision thresholds and strictly controls the weighing environment, keeping the weighing error within ±0.01 mg, matching the high precision requirements of the semiconductor industry for material parameters.

[0067] In steps S2-S3, the entire process of transferring samples between processes is completed in a drying oven with a relative humidity of ≤10%, and the connection time between adjacent processes does not exceed 30 minutes. Direct exposure to a conventional laboratory environment is prohibited.

[0068] In step S2, the samples are placed in a 304 stainless steel mesh carrier with a mesh aperture of 1-2 mm. Samples must not touch each other or be stacked. Semiconductor packaged samples are multi-phase three-dimensional structures with solder balls and leads; stacking or enclosed carriers can lead to uneven heating and prevent moisture dissipation, resulting in incomplete drying. The mesh carrier ensures full contact between the upper and lower surfaces of the sample and the hot airflow, simulating the uniform heating state of packaged devices in actual production. The sampling rules are as follows: the first weighing point is after 48 hours of baking, and subsequent weighings are taken every 12 hours, with each weighing session lasting no more than 5 minutes. If any sample shows abnormal conditions such as solder ball detachment or breakage, that group of samples is discarded and resampled for testing.

[0069] In step S3, a low-speed uniform airflow is used inside the moisture absorption chamber. The sample surface must not come into contact with the liquid water inside the chamber to avoid non-bulk moisture absorption phenomena such as surface condensation and capillary adsorption. This ensures that the test results reflect the diffusion and moisture absorption characteristics of the encapsulation material itself, rather than surface adsorption errors. The sampling rules are as follows: the first 24 hours of moisture absorption is the intensive data collection period, with samples taken and weighed at three fixed points: 8h, 16h, and 24h. After the initial 24 hours of moisture absorption is completed, samples are taken and weighed every 24 hours. After the cumulative moisture absorption time reaches 192 hours, samples are taken every 24 hours, with a maximum total moisture absorption time of 200 hours. If the maximum time is reached and moisture saturation is not determined, the test is terminated and noted in the test report. The moisture absorption process of the semiconductor epoxy encapsulation material conforms to the Fick diffusion law, with a fast moisture absorption rate and a large curve slope in the early stage, and gradually tending to saturate in the later stage. Intensive sampling in the first 24 hours can accurately capture data during the diffusion rise phase, ensuring the accuracy of subsequent calculations of half-saturation time and moisture diffusion rate; setting the longest moisture absorption time is to avoid indefinite testing and to align with the industry's standard testing cycle.

[0070] In step S4, the sampling rules are as follows: the 24 hours before baking is the intensive data collection period, and samples are taken and weighed at three fixed nodes at 8h, 12h and 24h; after the initial 24 hours of baking, samples are taken and weighed once every 12 hours; the weighing operation time between all adjacent nodes is controlled within 5 minutes.

[0071] In step S5, the calculation methods for reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount, and moisture diffusivity are as follows:

[0072] Reversible saturated moisture absorption mass: ;

[0073] Irreversible moisture absorption capacity: ;

[0074] Moisture absorption by saturated volume: ;

[0075] Moisture diffusivity: ;

[0076] in,

[0077] Total sample volume, in units of ;

[0078] The average thickness of the sample, in units of ;

[0079] The first dry weight, in units of ;

[0080] This is the saturated moisture-absorbing weight, in units of ;

[0081] This is the second dry weight, in units of ;

[0082] Temperature T, relative humidity Reversible saturated hygroscopic mass under the given conditions, in units of ;

[0083] The mass of irreversible moisture absorption is expressed in units of... ;

[0084] The half-saturation time is expressed in units of 1 / 2 oz. ;

[0085] This represents the saturated volumetric moisture absorption under corresponding temperature and humidity conditions, in units of... ;

[0086] D(T) is the water diffusivity at temperature T, in units of... .

[0087] Among them, reversible saturated hygroscopic mass corresponds to the total amount of physically adsorbed water in the packaging material that can be removed by baking. It is the direct source of moisture expansion pressure during reflow soldering and a core input parameter for MSL rating and reflow cracking risk assessment. Irreversible hygroscopic mass corresponds to the moisture permanently retained by the material due to chemical bonding and hydrolysis reactions under humid and hot environments. It is directly related to the long-term aging of the packaging material and the attenuation of interfacial adhesion strength, and is a key assessment indicator for high-reliability automotive electronics and military semiconductor devices. Saturated volumetric hygroscopic mass, also known as saturated water solubility, is one of the core material parameters for semiconductor reliability hygroscopic simulation. Volumetric hygroscopic mass can be directly imported into simulation software to calculate the moisture concentration distribution at different locations inside the package and predict the risk of delamination failure. Moisture diffusivity is a core parameter characterizing the rate of moisture penetration inside the material and is an essential input for hygroscopic simulation and shop floor life calculation. The one-dimensional diffusion assumption fits the current mainstream thin plastic-encapsulated device shape. The moisture diffusion of most planar packaged devices can be approximated as one-dimensional diffusion along the thickness direction, making it highly practical in engineering. In practical applications, the formula for calculating the water diffusivity is derived based on Fick's second law and Crank's one-dimensional diffusion model. It is only applicable to applications involving uniformly thick sheet-like semiconductor packaged samples, isotropic materials, and one-dimensional unidirectional water diffusion.

[0088] After completing the parameter calculation in step S5, the moisture absorption performance of semiconductor packaging materials can be quantitatively evaluated from three dimensions:

[0089] Saturated moisture absorption capacity: The core indicator is the saturated volumetric moisture absorption. The higher the value, the greater the saturated water absorption of the material, the higher the risk of delamination and cracking during reflow soldering, and the worse the moisture resistance. Under the conditions of 30℃ and 60%RH: <3mg / cm³ is the excellent grade for low moisture absorption; 3~5mg / cm³ is the acceptable grade for medium moisture absorption; >5mg / cm³ is the poor grade for high moisture absorption.

[0090] Moisture absorption rate: The core indicator is the moisture diffusivity. A higher value indicates faster moisture penetration and a shorter shelf life in the workshop. At 30℃: <1.5×10⁻ 6 mm² / s is considered excellent for slow speeds; 1.5~5×10⁻ 6 mm² / s is considered a medium-speed acceptable level; >5×10⁻ 6 mm² / s is considered a relatively poor rate of increase.

[0091] Long-term damp heat resistance reliability: The core indicator is the proportion of irreversible moisture absorption mass to dry weight. The higher the value, the higher the risk of long-term damp heat aging of the material. <0.001% is excellent, meeting the high reliability requirements of automotive, military and other applications; 0.001%~0.005% is acceptable, suitable for general consumer electronics; >0.005% is poor.

[0092] The risk of moisture sensitivity can be comprehensively determined by combining the saturated volumetric moisture absorption (SML) and the moisture diffusivity: low SML indicates low risk and excellent MSL level; high SML indicates high risk and poor MSL level.

[0093] Example 1:

[0094] This embodiment provides a more detailed description of the present invention based on actual test data of a certain sample, but the scope of protection of the present invention is not limited thereto.

[0095] This embodiment uses the evaluation method described in this invention to complete the full-process moisture absorption performance test and parameter calculation for semiconductor package sample #1. The specific implementation steps are as follows:

[0096] Step S1, Sample preparation and instrument calibration:

[0097] Semiconductor package sample #1 was selected. The initial total weight of the sample was 11.03072g, or 11030.72mg. Basic parameter measurements were completed before initial dehumidification: total sample volume. The average thickness of the sample was determined by averaging measurements taken at 5 points. .

[0098] The testing equipment used is a balance with an accuracy of 0.01 mg. The balance is placed on a level, vibration-free workbench and preheated, leveled, and zeroed 60 minutes in advance. The laboratory environment is maintained at 25℃ and 43%RH relative humidity. During weighing, the ion fan is turned off and personnel movement is prohibited to ensure that the weighing error is controlled within ±0.01 mg.

[0099] Step S2, initial dehumidification, i.e., the first stage of drying:

[0100] Sample #1 was placed in a 304 stainless steel mesh carrier, with no contact or stacking of samples, and then placed in a 125℃ constant temperature oven. The relative humidity inside the oven was controlled at 4%RH in real time. The test sampling and data recording are as follows:

[0101] like Figure 5 As shown, the initial weight of the sample at the baking start point T0 was 11.03072g.

[0102] 48-hour sampling: 2025.08.09 13:40, sample weight 11.02207g;

[0103] 60-hour sampling: 2025.8.1001:45, sample weight 11.02122g, adjacent weight change rate 0.0077%;

[0104] 72-hour sampling: 2025.8.10 13:50, sample weight 11.02100g, adjacent weight change rate 0.0020%;

[0105] 84-hour sampling: 2025.8.11 01:54, sample weight 11.02082g, adjacent weight change rate 0.0016%;

[0106] 96-hour sampling: 2025.8.11 13:59, sample weight 11.02073g, adjacent weight change rate 0.0008%;

[0107] When the baking time reaches 96 hours, the weight change rate of two consecutive adjacent weighings is less than 0.002%, and the weight change curve has entered the linear stable stage, which meets the drying endpoint determination criteria of this invention. Therefore, the initial dehumidification is determined to be complete, and the first dried weight of the sample at this time is recorded. .

[0108] After the initial dehumidification is completed, the sample is transferred to the constant temperature and humidity absorption chamber within 20 minutes, which meets the requirement of the present invention that the connection time is ≤30 minutes.

[0109] Step S3, constant temperature and humidity moisture absorption:

[0110] The #1 sample, which had undergone initial dehumidification, was placed in a constant temperature and humidity chamber at 30℃ and 60% relative humidity for moisture absorption testing. The sample surface did not come into contact with liquid water. The specific sampling and data recording are as follows:

[0111] like Figure 6 As shown, the initial moisture absorption weight of the sample at the moisture absorption starting point 0H was 11.02073g, which was exactly the same as the first drying weight, with no mid-term moisture absorption error.

[0112] 8-hour sampling: 2025.8.11 22:23, sample weight 11.02470g, cumulative moisture absorption 3.97mg;

[0113] Sampling at 16 hours: 2025.8.12 06:28, sample weight 11.02508g, cumulative moisture absorption 4.35mg;

[0114] 24-hour sampling: 2025.8.12 14:33, sample weight 11.02581g, cumulative moisture absorption 5.08mg;

[0115] 48-hour sampling: 2025.8.13 14:37, sample weight 11.02758g, cumulative moisture absorption 6.85mg;

[0116] 72-hour sampling: 2025.8.14 14:42, sample weight 11.02855g, cumulative moisture absorption 7.82mg;

[0117] 96-hour sampling: 2025.8.15 14:47, sample weight 11.02970g, cumulative moisture absorption 8.97mg;

[0118] 120-hour sampling: 2025.8.16 14:52, sample weight 11.03063g, cumulative moisture absorption 9.90mg;

[0119] 144-hour sampling: 2025.8.17 14:57, sample weight 11.03114g, cumulative moisture absorption 10.41mg;

[0120] Sampling at 168 hours: 2025.8.18 15:02, sample weight 11.03143g, cumulative moisture absorption 10.70mg;

[0121] Sampling at 192 hours: 2025.8.19 15:07, sample weight 11.03185g, cumulative moisture absorption 11.12mg;

[0122] Sampling at 216 hours: 2025.8.2015:12, sample weight 11.03234g, cumulative moisture absorption 11.61mg;

[0123] 240-hour sampling: 2025.8.21 15:17, sample weight 11.03270g, cumulative moisture absorption 11.97mg;

[0124] 264-hour sampling: 2025.8.22 15:22, sample weight 11.03295g, cumulative moisture absorption 12.22mg;

[0125] Sampling at 288 hours: 2025.8.23 15:27, sample weight 11.03315g, cumulative moisture absorption 12.42mg;

[0126] 312-hour sampling: 2025.8.24 15:32, sample weight 11.03331g, cumulative moisture absorption 12.58mg.

[0127] When the moisture absorption reaches 312 hours, the weight change rate of two consecutive adjacent weighings is less than 0.002%, and the moisture absorption curve has entered the linear stable stage, meeting the moisture absorption saturation endpoint determination criteria of this invention. Therefore, moisture absorption saturation is determined to be complete, and the saturated moisture absorption weight of the sample at this point is recorded. .

[0128] After moisture absorption saturation is completed, the sample is transferred to the final dehumidification oven within 13 minutes, which meets the requirement of the present invention that the connection time is ≤30 minutes.

[0129] Step S4, final dehumidification, i.e., the second stage of drying:

[0130] The moisture-saturated #1 sample was placed in a 125℃ constant temperature oven for final dehumidification and baking. The specific sampling and data recording are as follows:

[0131] like Figure 7 As shown, the baking start point 0H: the initial weight of the sample was 11.03331g, which is completely consistent with the saturated moisture-absorbing weight.

[0132] 8-hour sampling: 2025.8.24 23:48, sample weight 11.02325g, moisture content 2.52mg;

[0133] 12-hour sampling: 2025.8.25 03:52, sample weight 11.02247g, moisture content 1.74mg;

[0134] 24-hour sampling: 2025.8.25 16:55, sample weight 11.02181g, moisture content 1.08mg;

[0135] 36-hour sampling: 2025.8.26 04:59, sample weight 11.02135g, moisture content 0.62mg;

[0136] 48-hour sampling: 2025.8.26 17:03, sample weight 11.02113g, moisture content 0.40mg;

[0137] 60-hour sampling: 2025.8.27 05:06, sample weight 11.02095g, moisture content 0.22mg;

[0138] 72-hour sampling: 2025.8.27 17:10, sample weight 11.02084g, moisture content 0.11mg;

[0139] 84-hour sampling: 2025.8.2805:13, sample weight 11.02075g, moisture content 0.02mg.

[0140] When baking reaches 84 hours, the total baking time has exceeded the lower limit of 48 hours, and the weight change rate of two consecutive adjacent weighings is less than 0.002%, indicating that the weight change curve has entered a linear stable stage. This meets the final drying endpoint determination criteria of the present invention, and the final dehumidification is determined to be complete. The second dried weight of the sample at this point is recorded. Complete the entire process of test data collection.

[0141] Step S5, Calculation of water diffusivity and water solubility:

[0142] Based on the above experimental data and basic sample parameters, calculations were performed according to standardized formulas, and the half-saturation time was solved using linear interpolation.

[0143] Reversible saturated moisture absorption mass:

[0144] ;

[0145] Irreversible moisture absorption capacity:

[0146] ;

[0147] The evaluation was based on the reversible saturated moisture absorption mass: the irreversible moisture absorption mass is close to 0, indicating that the encapsulation material does not permanently absorb moisture under the test temperature, humidity, and baking conditions, and the material has good thermal stability and moisture resistance.

[0148] Saturated volume moisture absorption:

[0149]

[0150] Half-saturation time:

[0151] Based on the moisture absorption curve data, the reversible saturated moisture absorption mass of sample #1 is... The semi-saturated moisture absorption capacity is Two sets of node data with a moisture absorption rate close to 6.28 mg were selected:

[0152] After 48 hours of moisture absorption: moisture absorption capacity 6.85 mg;

[0153] Moisture absorption 24h: moisture absorption capacity 5.08mg;

[0154] Using linear interpolation, when the moisture absorption reaches 6.28 mg, the corresponding moisture absorption time is approximately 38 hours, or 136,800 seconds. Therefore, the half-saturation time... .

[0155] Moisture diffusivity:

[0156] Given: , Substitute into the formula:

[0157]

[0158] Saturated volume moisture absorption It is classified as medium moisture absorption grade;

[0159] Irreversible moisture absorption The value is close to 0 and far below 0.001%, which is considered excellent.

[0160] Moisture diffusivity D≈2.00×10⁻ 6 mm² / s represents a medium-low diffusion rate, close to the excellent range.

[0161] The packaging material exhibits excellent long-term resistance to damp heat aging and poses no risk of permanent moisture absorption. Its saturated moisture absorption is at a moderate level, and its moisture absorption rate is relatively slow. Overall, it has good moisture resistance and can meet the reliability requirements of industrial-grade and automotive-grade packaging. The corresponding MSL level can typically reach level 2 to 3, and the pressure of workshop life control is moderate.

[0162] This embodiment strictly follows the operating specifications, sampling rules, endpoint determination criteria, and calculation formulas of this invention throughout the entire process. The testing procedure is compliant, and the data is reproducible. The obtained parameters such as reversible hygroscopic mass, saturated volume hygroscopic capacity, and moisture diffusivity can be directly used for determining the MSL humidity sensitivity level, packaging structure design, and reliability simulation of this semiconductor packaging material.

Claims

1. A method for evaluating the moisture absorption properties of semiconductor packaging materials, characterized in that: Includes the following steps: S1, Sample preparation: Select semiconductor packaged samples and record initial sample data; S2, Initial Dehumidification: Place the sample in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH and bake it. Take samples and weigh them at the set time points, determine the drying endpoint according to the unified criteria, and record the first drying weight. S3, Constant temperature and humidity dehumidification: Place the sample that has completed the initial dehumidification in a dehumidification chamber with a temperature of 30±10℃ and a relative humidity of 60±10%. Take samples and weigh them according to the grading rules of the intensive sampling period and the stable period. Determine the dehumidification saturation endpoint according to the unified criteria and record the saturated dehumidification weight. S4, final dehumidification: Place the moisture-saturated sample in a constant temperature oven at 125±10℃ and internal relative humidity ≤5%RH for more than 48 hours, take samples and weigh them according to the set time nodes, determine the drying endpoint according to the unified criteria, and record the second drying weight. S5, Standardized parameter calculation: Based on the data collected in steps S1 to S4, the reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount and moisture diffusivity of the sample are calculated. S6, Result Evaluation: Evaluate the material's moisture absorption performance based on the calculation results of step S5. The higher the saturated volume moisture absorption, the worse the material's moisture resistance; the higher the moisture diffusivity, the faster the material's moisture absorption rate; the higher the irreversible moisture absorption mass, the higher the risk of long-term damp heat aging of the material. In steps S2-S4, the unified criterion is the determination condition for the drying or moisture absorption endpoint. Meeting any one of the following conditions is sufficient to determine that the corresponding endpoint has been reached: The weight change rate of at least two consecutive weighing data does not exceed 0.002%; The weight-time change curve has entered a linear steady-state phase; The formula for calculating the single-weight change rate is: Single-weight change rate = (current weighing mass - previous weighing mass) / previous weighing mass × 100%.

2. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S1, the initial sample data includes sample weight, total sample volume, and average sample thickness.

3. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S1, the total weight of the sample is not less than 10g, the number of samples is not less than 5, and there are no air bubbles or impurities; the total volume of the sample is measured by the water displacement method; the average thickness of the sample is obtained by taking the arithmetic mean after measuring 5 different points on the sample.

4. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S1, an electronic balance that meets the accuracy requirements is used to complete the balance preheating, leveling calibration and zeroing operations under a specified environment, and a clean and dry container is used for weighing.

5. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In steps S2-S3, the entire process of transferring the sample between processes is completed in a drying oven with a relative humidity of ≤10%, and the connection time between adjacent processes does not exceed 30 minutes.

6. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S2, the sampling rules are as follows: the first weighing point is after baking for 48 hours, and subsequent weighing is carried out every 12 hours, with each weighing session lasting no more than 5 minutes; if the sample shows abnormal conditions such as solder ball detachment or breakage, the sample group is discarded and resampled for testing.

7. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S3, a low-speed uniform airflow is used inside the moisture absorption chamber, and the sample surface must not come into contact with liquid water inside the chamber. The sampling rules are as follows: the first 24 hours of moisture absorption is the intensive data collection period, and samples are taken and weighed at three fixed points: 8h, 16h, and 24h. After the initial 24 hours of moisture absorption is completed, samples are taken and weighed every 24 hours. After the cumulative moisture absorption time reaches 192 hours, samples are taken every 24 hours. The maximum total moisture absorption time is 200 hours. If the maximum time is reached and the moisture absorption is still not determined to be saturated, the test is terminated and noted in the test report.

8. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S4, the sampling rules are as follows: the 24 hours before baking is the intensive data collection period, and samples are taken and weighed at three fixed nodes at 8h, 12h, and 24h; after the initial 24 hours of baking, samples are taken and weighed once every 12 hours; the weighing operation time between all adjacent nodes is controlled within 5 minutes.

9. The method for evaluating the moisture absorption properties of a semiconductor packaging material according to claim 1, characterized in that: In step S5, the calculation methods for reversible saturated hygroscopic mass, irreversible hygroscopic mass, saturated volume hygroscopic amount, and moisture diffusivity are as follows: Reversible saturated moisture absorption mass: ; Irreversible moisture absorption capacity: ; Moisture absorption by saturated volume: ; Moisture diffusivity: ; in, Total sample volume, in units of ; The average thickness of the sample, in units of ; The first dry weight, in units of ; This is the saturated moisture-absorbing weight, in units of ; This is the second dry weight, in units of ; Temperature T, relative humidity Reversible saturated hygroscopic mass under the given conditions, in units of ; The mass of irreversible moisture absorption is expressed in units of... ; The half-saturation time is expressed in units of 1 / 2 oz. ; This represents the saturated volumetric moisture absorption under corresponding temperature and humidity conditions, in units of... ; D(T) is the water diffusivity at temperature T, in units of... .